Perlindungan Hukum terhadap Tenaga Kerja Dihubungkan dengan Prinsip Kesetaraan Upah yang Sama dalam Pemberian Upah di Indonesia - Mirabel Rahma Nesiabila; Deni Yusup Permana (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze worker wage regulations based on Indonesian positive law and worker protection in relation to the principle of equal pay in Indonesia. The research method used is a normative juridical approach. The results of the study indicate that wage regulations are regulated in Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning Job Creation and Government Regulation Number 36 of 2021 concerning Wages. However, violations of the principle of equal pay are still found, such as wage differences between workers with the same workload and responsibilities without any objective basis. Furthermore, the lack of transparency in wage structures and scales and the absence of written employment agreements.